2022
DOI: 10.1186/s12913-022-08074-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of first wave of COVID-19 outbreak on routine healthcare services, Liberia, August 2020: a mixed study approach

Abstract: Background The COVID-19 pandemic left countries to rapidly implement diverse and stringent public health measures without recourse to mitigate its effect on the sustenance of routine healthcare services. This study described routine health service disruption and restoration strategies at 6 months into the epidemic in Liberia. Methods Liberia, with 15 counties, has 839 health facilities, with one-third in Montserrado County. A cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Several studies reported on the reduction of fixed services, outreach services and service utilisation. Four studies reported a decline in fixed services provided during the study period [ 18 , 37 , 38 , 59 ]. Another four studies also reported a decline in or limited outreach services provided [ 18 , 37 , 38 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported on the reduction of fixed services, outreach services and service utilisation. Four studies reported a decline in fixed services provided during the study period [ 18 , 37 , 38 , 59 ]. Another four studies also reported a decline in or limited outreach services provided [ 18 , 37 , 38 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported a decline in fixed services provided during the study period [ 18 , 37 , 38 , 59 ]. Another four studies also reported a decline in or limited outreach services provided [ 18 , 37 , 38 , 58 ]. For example, Babalola et al found that fixed services were offered by 92% of facilities included in the Liberian study, but there was a 47% decline in outreach services [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 epidemic reached Liberia in 2020 ( 25 ), ~6 years after EVD devastated the country's health system and created the first opportunity to test health facility readiness capacities to respond to a large-scale epidemic while retaining routine health services. Despite the national response to the epidemic, COVID-19 rapidly spread across the country and is believed to have affected a large proportion of the population, but the exact extent is unknown due to low testing capacity and mild symptoms in the majority of cases ( 26 ).…”
Section: Introductionmentioning
confidence: 99%